Thrombosis of the External Jugular Vein: A Rare Complication of a Proximal Humerus Fracture Treated with Collar and Cuff Immobilisation - Michael Gale; Simon Craxford; Leia Taylor; Helen Montgomery; Simon Pickering (Case Reports in Orthopedics)
We report the case of an 87-year-old woman who developed a thrombosis of her external jugular vein after sustaining a proximal humerus fracture managed nonoperatively with a collar and cuff. At review in fracture clinic she was found to have an enlarged external jugular vein which was subsequently found to be thrombosed. Her collar and cuff had been applied very tightly and it was felt by the ENT team to be the cause of the thrombosis of her external jugular vein. She was fully anticoagulated with warfarin after subsequently developing a deep vein thrombosis in the subclavian and axillary veins. She made a full recovery following anticoagulation. In this case, we review the potential causes of this rare and underdiagnosed condition, as well as the usual investigations and treatments. We also review the common complications of this fracture and the alternative treatment options available.